Nuclear Factor I in neurons, glia and during the formation of Müller glia‐derived progenitor cells in avian, porcine and primate retinas. Issue 8 (15th December 2021) - El‐Hodiri, Heithem M.; Campbell, Warren A.; Kelly, Lisa E.; Hawthorn, Evan C.; Schwartz, Maura; Jalligampala, Archana; McCall, Maureen A.; Meyer, Kathrin; Fischer, Andy J.
Abstract: The regenerative potential of Müller glia (MG) is extraordinary in fish, poor in chick and terrible in mammals. In the chick model, MG readily reprogram into proliferating Müller glia‐derived progenitor cells (MGPCs), but neuronal differentiation is very limited. The factors that suppress the neurogenic potential of MGPCs in the chick are slowly being revealed. Isoforms of Nuclear Factor I (NFI) are cell‐intrinsic factors that limit neurogenic potential; these factors are required for the formation of MG in the developing mouse retina and deletion of these factors reprograms MG into neuron‐like cells in mature mouse retina. Accordingly, we sought to characterize the patterns of expression of NFIs in the developing, mature and damaged chick retina. In addition, we characterized patterns of expression of NFIs in the retinas of large mammals, pigs and monkeys. Using a combination of single‐cell RNA‐sequencing (scRNA‐seq) and immunolabeling, we probed for patterns of expression. In embryonic chick, levels of NFIs are very low in early E5 (embryonic day 5) retinal progenitor cells (RPCs), upregulated in E8 RPCs, further upregulated in differentiating MG at E12 and E15. NFIs are maintained in mature resting MG, microglia and neurons. Levels of NFIs are reduced in activated MG in retinas treated with NMDA and/or insulin+FGF2, and further downregulated in proliferating MGPCs. However, levels of NFIs in MGPCs were significantly higher than those seen in RPCs. Immunolabeling for NFIA and NFIB closely matched patterns of expression revealed in different types of retinal neurons and glia, consistent with findings from scRNA‐seq. In addition, we find expression of NFIA and NFIB through progenitors in the circumferential marginal zone at the far periphery of the retina. We find similar patterns of expression for NFIs in scRNA‐seq databases for pig and monkey retinas. Patterns of expression of NFIA and NFIB were validated with immunofluorescence in pig and monkey retinas wherein these factors were predominantly detected in MG and a few types of inner retinal neurons. In summary, NFIA and NFIB are prominently expressed in developing chick retina and by mature neurons and glia in the retinas of chicks, pigs and monkeys. Although levels of NFIs are decreased in chick, in MGPCs these levels remain higher than those seen in neurogenic RPCs. We propose that the neurogenic potential of MGPCs in the chick retina is suppressed by NFIs. Abstract : In the chick model, Müller glia (MG) readily reprogram into proliferating Müller glia‐derived progenitor cells (MGPCs), but neuronal differentiation is limited. Isoforms of Nuclear Factor I (NFI) are cell‐intrinsic factors that limit neurogenic potential. We investigated expression of NFIs in chicken, pig and monkey retinas using single‐cell RNA seq (scRNA seq) and immunofluorescence. We found similar patterns of expression across chick, pig and monkey retinas. In the chick, NFIs are expressed in MG and some neurons as they develop, mature MG, and that expression decreases during the activation of MG and MGPC formation. Our results are consistent with a role for NFIs in suppressing neurogenic potential in MGPCs.